Presleep Alpha-lactalbumin consumption does not improve sleep quality or time-trial performance in cyclists - MacInnis, M. J.; Dziedzic, C. E.; Wood, E.; Oikawa, S. Y.; Phillips, S. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
We tested the hypothesis that presleep consumption of alpha-lactalbumin (LA), a fraction of whey with a high abundance of tryptophan, would improve indices of sleep quality and time-trial (TT) performance in cyclists relative to an isonitrogenous collagen peptide (CP) supplement lacking tryptophan. Using randomized, double-blind, crossover designs, cyclists consumed either 40 g of LA or CP 2 hr prior to sleep. In Study 1, six elite male endurance track cyclists (age 23 ± 6 years, VO2peak 70.2 ± 4.4 ml·kg-1·min-1) consumed a supplement for three consecutive evenings before each 4-km TT on a velodrome track, whereas in Study 2, six well-trained cyclists (one female; age 24 ± 5 years, VO2peak 66.9 ± 8.3 ml·kg-1·min-1) consumed a supplement the evening before each 4-km TT on a stationary cycle ergometer. Indices of sleep quality were assessed with wrist-based actigraphy. There were no differences between the CP and LA supplements in terms of total time in bed, total sleep time, or sleep efficiency in Study 1 (LA: 568 ± 71 min, 503 ± 67 min, 88.3% ± 3.4%; CP: 546 ± 30 min, 479 ± 35 min, 87.8% ± 3.1%; p = .41, p = .32, p = .74, respectively) or Study 2 (LA: 519 ± 90 min, 450 ± 78 min, 87.2% ± 7.6%; CP: 536 ± 62 min, 467 ± 57 min, 87.3% ± 6.4%; p = .43, p = .44, p = .97, respectively). Similarly, time to complete the 4-km TT was unaffected by supplementation in Study 1 (LA: 274.9 ± 7.6 s; CP: 275.5 ± 7.2 s; p = .62) and Study 2 (LA: 344.3 ± 22.3 s; CP: 343.3 ± 23.0 s; p = .50). Thus, relative to CP, consuming LA 2 hr prior to sleep over 1-3 days did not improve actigraphy-based indices of sleep quality or 4-km TT performance in cyclists.